2020
DOI: 10.47391/jpma.1046
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of breast self-examination among female undergraduate medical students in Poonch Medical College, Azad Kashmir

Abstract: Abstract A cross-sectional observational study was conducted to assess the knowledge, attitude, and practice (KAP) of breast self-examination (BSE) among female undergraduate medical students in Poonch Medical College, Azad Kashmir. Out of 306 respondents, 250 completed the 16-item questionnaire (response rate of 81.7%). The correlations between knowledge, attitude, and practice were observed. Out of the total 250 respondents, 180 (72.0%) had ever heard of BSE, and 62 (24.8%) had performed BSE. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, a gap between knowledge and practice was also seen, as 45.1% knew about BSE, whereas only 33.3% performed it [ 17 ]. Likewise, 91% of students believed that BSE is essential, but only 87% of students could perform it [ 21 ]. Similarly to the finding that most participants (71%) had BSE-related knowledge, 60% knew how BSE must be performed, but only 16% performed it regularly [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a gap between knowledge and practice was also seen, as 45.1% knew about BSE, whereas only 33.3% performed it [ 17 ]. Likewise, 91% of students believed that BSE is essential, but only 87% of students could perform it [ 21 ]. Similarly to the finding that most participants (71%) had BSE-related knowledge, 60% knew how BSE must be performed, but only 16% performed it regularly [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Not considering it necessary was also suggested by several studies. Specifically, 4.54% of medical students [ 21 ], contrasting to 13.3% of respondents, thought BSE was unnecessary and expressed fear of receiving a BC diagnosis [ 19 ]. This finding is similar to another study where 11.8% disagreed that BSE was essential [ 48 ] and did not consider it useful [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were seen in a study among nursing students in Turkey and medical students in Ethiopia and Ghana [ 11 , 12 , 22 ]. Contrarily, studies among medical students from Iran and Kashmir and non-medical students from Turkey, Malaysia, and Bangladesh reported lesser percentages of BSE practice [ 14 , 15 , 20 , 21 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, type of family, good knowledge of BC risk factors, and being taught the technique of BSE by healthcare staff, family, or other teaching faculty were significantly associated with regular BSE. In a similar vein, studies done in health sciences colleges in Ethiopia, Kashmir, and Turkey found years of university study, family history of BC, and knowledge of BC to be significantly associated with the practice of BSE to significantly improve the chances of performing BSE regularly [11,14,22]. On the contrary, among nonmedical university students across the world, apart from good knowledge, age, marital status, having a good attitude towards BSE, being urban residents, and social status were found to be significantly associated with the practice of BSE [15,17,18,21].…”
Section: Factors Significantly Associated With Bse Practicementioning
confidence: 93%
See 1 more Smart Citation